Funkcje założone i rzeczywiste promotora pomocniczego w dysertacjach doktorskich = The assummed and the real functions of auxiliary supervisor in Phd dissertations - Śliwerski, Bogusław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the article I present a multidimensional analysis of the Act of 18 March 2011 on the amendment of the Act - The Law on higher education, The Act on academic degrees and academic titles as well as on degrees and titles related to art study - in particular - a new academic role in Phd studies, defined as auxiliary supervisor. In 2014 it underwent an amendment, which has not changed anything in this case, despite numerous critical opinions towards solutions introduced as an amendment in 2011.
Keywords: szkolnictwo wyższe; ustawa; promotor pomocniczy; szkoła doktorska; przewód doktorski